2017
DOI: 10.1016/j.jdiacomp.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of nonalcoholic fatty liver disease: Potential role for 12-lipoxygenase

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a spectrum of pathologies associated with fat accumulation in the liver. NAFLD is the most common cause of liver disease in the United States, affecting up to a third of the general population. It is commonly associated with features of metabolic syndrome, particularly insulin resistance. NAFLD shares the basic pathogenic mechanisms with obesity and insulin resistance, such as mitochondrial, oxidative and endoplasmic reticulum stress. Lipoxygenases catalyze the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 108 publications
0
19
0
2
Order By: Relevance
“…Extensive evidence suggests that oxidative stress play a pivotal role in the disease progression from simple steatosis to steatohepatitis and irreversible damage to the liver . Multiple clinical studies have demonstrated the elevated levels of circulating products of oxidative stress and lipid peroxidation such as malondialdehyde (MDA), oxidized LDL (ox‐LDL), and thiobarbituric acid‐reacting substances (TBARS), as well as depletion of cellular antioxidants, in patients with NAFLD and NASH compared with age‐matched controls . However, the relationship between the extent of steatosis and oxidative stress biomarkers, independent of obesity, has not been previously investigated, as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive evidence suggests that oxidative stress play a pivotal role in the disease progression from simple steatosis to steatohepatitis and irreversible damage to the liver . Multiple clinical studies have demonstrated the elevated levels of circulating products of oxidative stress and lipid peroxidation such as malondialdehyde (MDA), oxidized LDL (ox‐LDL), and thiobarbituric acid‐reacting substances (TBARS), as well as depletion of cellular antioxidants, in patients with NAFLD and NASH compared with age‐matched controls . However, the relationship between the extent of steatosis and oxidative stress biomarkers, independent of obesity, has not been previously investigated, as well.…”
Section: Introductionmentioning
confidence: 99%
“…8 Multiple clinical studies have demonstrated the elevated levels of circulating products of oxidative stress and lipid peroxidation such as malondialdehyde (MDA), oxidized LDL (ox-LDL), and thiobarbituric acid-reacting substances (TBARS), as well as depletion of cellular antioxidants, in patients with NAFLD and NASH compared with age-matched controls. [9][10][11] However, the relationship between the extent of steatosis and oxidative stress biomarkers, independent of obesity, has not been previously investigated, as well. Therefore in the present study, we have determined whether the presence of different liver steatosis grades is related to the oxidative stress and antioxidant status biomarkers in NAFLD patients compared with a group of healthy obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, linolenic acid, a polyunsaturated omega-6 fatty acid, is important in the biosynthesis of AA and therefore, some prostaglandins, leukotrienes (LTA 4 , LTB 4 , LTC 4 ), and thromboxane (TXA 2 ). Previous study showed that arachidonic acid and linoleic acid were mianly poly-unsaturated fatty acids in the plasma membrane which could produce oxidized pro-inflammatory lipid intermediates with the conversion by lipoxygenases catalyze (Samala et al, 2017 ). In our study, the level of these poly-unsaturated fatty acids in control group is higher than that in disease group.…”
Section: Discussionmentioning
confidence: 99%
“…This model is also supported by the lack of effect of GW9662 also on ALOXE3-induced thermogenesis. In addition, it should be recognized that genetic disruption of both 12-LOX and 15-LOX in multiple diabetic models largely recapitulates the ALOXE3-mediated enhancement of hepatic insulin sensitivity and reduced hepatic steatosis (15)(16)(17). Therefore, it is quite feasible that -in addition to generating the PPARg ligand 12-KETE -either ALOXE3 activity also depletes 12-LOX products 12-HpETE and 12-HETE ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a recent large cohort adults with type 2 diabetes demonstrated a potentially protective role for 5-lipoxygenases ALOX5 and ALOX5AP against diabetes mellitus (14). Conversely, ALOX12/15 inhibition in rodent models inhibited oxidative stress, b-cell deterioration, hepatic steatosis and systemic inflammation (15)(16)(17)(18). Together, these data suggest that intracellular lipid intermediary metabolism drives both tissue-level and whole-organism metabolic homeostasis.…”
Section: Introductionmentioning
confidence: 97%